Effect of modifiers on Fe-Pt/Al2O3 catalysts for alkanes hydrotreatment - Zhumabekova, A.K.; Tastanova, L.K.; Orynbassar, R.O.; Zakumbaeva, G.D. (KU publ., 2020)
Zeolite-containing polyfunctional catalysts Fe-Pt/Al2O3 (КТ-17, КТ-18), modified with additives of molybdenum, phosphorus and cerium, were synthesized. The developed catalytic systems were studied in treatment of C14 alkane obtaining a gasoline fraction. Reaction products contain C4-C9 iso-alkanes, C10-C14 isoalkanes, C4-C10 alkanes, aromatic hydrocarbons and C1-C3 alkanes. In addition, 0.2–0.6 % of heavy hydrocarbons was found in reaction products. The yield of C4-C9 iso-alkanes at 380 °C reached 37.9 %. By means of physical and chemical methods it has been found that the zeolite containing catalysts Fe-Pt /Al2O3 modified by various additives are complex systems. Micro-diffraction and Mossbauer spectroscopy methods allowed detecting nanosized hetero clusters of Fe-Pt, Fe-Mo, Pt-Mo in catalysts structure. Depending on chemical composition of clusters, particle size varies between 20 and 80 Ǻ. KT-18 catalyst demonstrates high activity in the process of heavy alkanes treatment; sizes of platinum (d = 200 Å) and iron (d = 30–50 Å) particles were determined by electron microscopy. Activity of KT-18 catalyst is higher than that of highly dispersed KT-17. The main feature of KT catalysts is their polyfunctionality. During alkanes processing simultaneous and consecutive reactions of hydrocracking, dehydrogenation, isomerization, dehydro-cyclization and hydro-desulfurization take place.
Модификаторлардың Fe-Pt/Al2O3 алкандарды гидроөңдеу катализаторларына əсері
Влияние модификаторов на Fe-Pt/Al2O3 катализаторы гидропереработки алканов
Keywords: hydro treatment; zeolite containing catalysts; modification; polyfunctionality; heavy alkanes; hydrocracking; hydrogenation; nanoclusters